Graphene-Mediated removal of Microcystin-LR in chitosan/graphene composites for treatment of harmful algal blooms. (August 2022) - Zetterholm, Sarah Grace; Gurtowski, Luke; Roberts, Jesse L.; McLeod, Sheila; Fernando, Brianna M.; Griggs, Chris S.
Abstract: Water quality can be severely impacted by algal blooms alone, yet cyanotoxins, such as microcystin (MC), are potent underlying hazards produced by various species of cyanobacteria. Currently there is a need for environmentally compatible and economically viable media to address large scale application for HAB impacted waters. This study evaluated the interactions of chitosan/graphene (CSG) composites with three different species of cyanobacteria: Anabaena sp, Synechocystis sp, and Microcystis aeruginosa for both removal of algal optical density and toxins. Although results suggest that CSG has an algae dependent removal of density with a range of 40–90% removal, graphene/CSG is highly effective at MC toxin removal, removing >94% of MC-LR produced by Microcystis aeruginosa . Characterization by SEM and XRD revealed that 750 m 2 /g surface area graphene, imparts graphene morphology and functionality into the chitosan matrix surface, potentially enabling π-π interactions between graphene and the aromatic ring of microcystin. This proposed π-π removal mechanism of microcystin via the CSG chitosan biopolymer substrate offers a promising sustainable and selective media suitable for deployable treatment of HAB impacted waters. Graphical abstract: Image 1 Highlights: High surface area graphene imparts graphene functionality to chitosan composites. Graphene nanoplatelets and composites efficiently remove MC-LR from water. π-π interactions between graphene and MC-LR are the dominating force for removal.